Maternal pesticides exposure in pregnancy and the risk of wheezing in infancy: A prospective cohort study. (May 2022) - Maritano, Silvia; Moirano, Giovenale; Popovic, Maja; D'Errico, Antonio; Rusconi, Franca; Maule, Milena; Richiardi, Lorenzo
Graphical abstract: Highlights: In an Italian birth cohort three indirect methods to assess pesticide exposure during pregnancy were used. The association of each of the maternal exposure variables with infant wheezing occurrence was evaluated. Self-reported pesticide use during pregnancy was weakly associated with infant wheezing. Involvement in agricultural activities during pregnancy was not associated with infant wheezing. In rural areas, living in proximity of crops, especially fruit trees, during pregnancy was associated with infant wheezing. Abstract: Introduction: Pesticide exposure in pregnancy may have health effects in the offspring. We studied whether maternal pesticides exposure during pregnancy is associated with infant wheezing. Methods: The study involved 5997 children from the Italian NINFEA birth cohort, whose mothers were recruited during pregnancy between 2005 and 2016. We used questionnaires completed during pregnancy and 6 months after delivery to derive the following indirect measures of exposure: i) Self-reported pesticide use during the first and the third trimester of pregnancy; (ii) Agricultural activities during the same trimesters. We also evaluated the exposure to agricultural pesticides applied near home using the Corine Land Cover inventory to derive the proportion of a 200-metre buffer area around maternal home address covered by agricultural crops and specific crop types (arable land, fruit trees, heterogeneous cultivations). Questionnaires completed when the child turned 18 months reported information on wheezing between 6 and 18 months of age. We estimated the odds ratios of wheezing adjusting for the following maternal characteristics: age, education, parity, asthma, atopy, smoking in pregnancy, region and area of residence, pet ownership during pregnancy. Crops proximity analyses were restricted to residents in rural areas (N = 1674). Results: Agricultural activities during pregnancy were not associated with infant wheezing. Compared to no pesticide use, there was a weak positive association for self-reported use in the third trimester (POR: 1.30; 95 %CI 0.95–1.78) and a stronger association for use in both trimesters (POR: 1.72; 95 %CI 1.11–2.65). The relationship between the proportion of crops around the home address and the risk of infant wheezing, was J-shaped, in particular for fruit trees with the lowest risk for mid values and elevated risk for higher values. Conclusion: We found some evidence of association for maternal pesticide use in pregnancy and residential proximity to fruit trees cultivations with infant wheezing.